STATE BORDERS VS. CULTURAL HISTORICAL AND RELIGIOUS SOCIAL NETWORKS: THE CASE OF TURKISH KURDS’, KURDS IN IRAQ - AND THEIR STRUGGLE FOR SELF DETERMINATION - Gabbay, Shaul M. (European Scientific Journal, ESJ, 2014)
There are estimated 30 million Kurdish people in the world today concentrated in Turkey, Iraq, Syria, Lebanon and Iran. Kurds constitute the largest stateless minority in the modern world. This paper poses several questions to be delineated and discussed further. I begin with a description of the Kurds in Turkey, their history, social and cultural identity, I move to the history of challenges they have faced since the inception of the Turkish state. I then discuss the current drawbacks for their lives in Turkey of today asking if the state borders will sustain the cultural, religious and strong social networks particularly with the latest changes in the Arab world and the Kurdish advancements in the Kurdish part of Iraq. The paper also delineates the Kurds’ circumstances in Iran, Iraq and Syria.